Cover Image, Volume 12, Issue 10. (8th October 2018) - Zheng, Lisha; Zhang, Lingyu; Chen, Luoping; Jiang, Jingyi; Zhou, Xiaocheng; Wang, Ming; Fan, Yubo
Abstract : The cover image is based on the Research Article Static magnetic field regulates proliferation, migration, differentiation, and YAP/TAZ activation of human dental pulp stem cells by Lisha Zheng et al., https://doi.org/10.1002/term.2737 .